Sistem Informasi Konsultasi Kesehatan Mental Santri Di Ponpes Djannatul Huda Berbasis Web Dengan Laravel - Ari Farah Furqon; Ihsan Nur Cahyo (Jurnal Media Computer Science, 2026)
Mental health is an important aspect that needs attention, especially in an Islamic boarding school environment that has high emotional and spiritual dynamics. However, the consultation system used is still manual and not well documented. This research aims to design and implement a web-based Student Mental Health Monitoring Consultation Information System (SiKonsul) at the Djannatul Huda Islamic Boarding School. The development method used is the Waterfall model with the stages of needs analysis, design, coding, testing, and maintenance. The system is developed using the Laravel framework, PHP programming language, and MySQL database, and is presented in the form of UML diagrams to facilitate system visualization. The test was carried out through Blackbox Testing and usability evaluation using the System Usability Scale (SUS). The test results of 32 respondents showed an average score of 86.25 which was classified as "Excellent", indicating that the system is very suitable for use and acceptance by users. Thus, SiKonsul is expected to be an effective digital solution in improving mental health consultation services in a sustainable manner in the pesantren environment.